PENGARUH KEPEMIMPINAN, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN SMK NEGERI 1 SURABAYA - Indayani, Desy; Zuswana, Aries (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
The objectives of this study are: (1) To determine whether leadership, motivation, and work environment factors partially have a significant influence on employees at SMK Negeri 1 Surabaya. (2) To determine whether leadership, motivation, and work environment factors collectively have a significant influence on employee performance at SMK Negeri 1 Surabaya. (3) To determine which factor, among leadership, motivation, and work environment, has the most dominant influence on employee performance at SMK Negeri 1 Surabaya. (4) Do leadership, motivation, and work environment factors simultaneously influence employee performance at SMK Negeri 1 Surabaya? The type of research used is quantitative research. The population in this study was 40 employees. The sampling method used saturated samples. The data collection technique used was a questionnaire. The data analysis technique used was validity test, reliability, multiple linear regression and T test. Based on the test results using SPSS analysis to test the influence of several variables on the performance of employees of SMK Negeri 1 Surabaya and some discussions of the results presented. With the research that has been done, it was found that Leadership (X1), Motivation (X2), and Work Environment (X3) have a positive effect on employee performance (Y) of SMK Negeri 1 Surabaya with an F count value of 744.643> F table 2.886. While partially the variable X1 has a sig. 0.035 <0.05 against Y, the variable X2 against Y has a sig. 0.001 <0.05, and the variable X3 has a sig. 0.008 < 0.05 on Y. Meanwhile, simultaneously there is a positive and significant influence between Leadership, Motivation, and Work Environment on Employee Performance at SMA Negeri 1 Surabaya. This is evidenced by the Sig. value of 0.000 < 0.05 and Fh > Ft = 744.643 > 2.866.